Social Determinants of Health in Non-communicable Diseases Case Studies from Japan - Kondo, Katsunori; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This open access book is the first compilation that reviews a wide range of social determinants of health (SDHs) for non-communicable diseases (NCDs) and healthy ageing in Japan. With the highest life expectancy and the largest elderly population in the world, Japan has witnessed health inequality by region and social class becoming more prevalent since the 2000s. The first half of this volume describes in detail major NCDs, such as cancers, heart and kidney diseases, diabetes, stroke, and metabolic syndrome. The second half, on the other hand, explores various SDHs relating to healthy ageing. All chapters review and focus on SDHs, particularly health inequality associated with socio-economic status and social capital, which are widely addressed in the field of social epidemiology. The book makes the argument that (3z(BHealth for All(3y (Badvocated by the WHO should be implemented based on social justice and benefits for the greater society. Public health researchers and policymakers, both in Japan and other nations, will gain scientific evidence from this book to prepare for the coming era as ageing becomes a global issue. Katsunori Kondo is Professor of Social Epidemiology and Health Policy, Center for Preventive Medical Sciences and the Graduate School of Medicine, Chiba University, Japan. He is also Head of Department of Gerontological Evaluation at the Center for Gerontology and Social Science, National Center for Geriatrics and Gerontology. .s
Acknowledgements -- Preface -- Table of Contents -- Editor Bio -- The Social Determinants of Health and Trends Concerning Health Disparity -- Behavioral Problems in Children -- Metabolic Syndorome -- Cancer and Socioeconomic Status -- Coronary Heart Disease -- Stroke -- Chronic kidney disease -- Diabetes Mellitus -- Suicide -- Depression -- Dementia -- Falls and Related Bone Fractures -- Malnutrition in Older People -- Oral Health -- Healthy aging:IADL and functional disability -- Life Course Epidemiology -- Social capital and health -- Access to Healthcare and Health Inequality -- Measures of Health Inequality and Health Impact Assessment -- What Measures Can Be Taken to Reduce Health Disparity? -- Recommendations -- Ministeral notification -- Monitoring report (1) -- Monitoring Report (3) -- Monitoring Report (5) -- Monitoring Report (8) -- Index.
Keywords: Medical economics; Social structure; Equality; Epidemiology; Medical policy; Health Economics; Social Structure; Epidemiology; Health Policy